NMR and molecular dynamics structural investigations of Manduca sexta stress response peptides and Anopheles gambiae ecdysis triggering hormone - Dembele, Hawa (Kansas State University, 2021)
Stress-responsive peptides (SRPs) represent a largely unexplored group of peptides within the class of Insecta that regulate cell chemotaxis, proliferation, and anti-microbial gene expression. The diverse functions of these peptides led us to undertake structure-activity relationship studies of Stress-Response Peptides 1 and 2 (SRP-1 and -2) secreted by the lepidopteran Manduca sexta in response to biotic and abiotic stressors. Mature SRP-1 and -2 contain 25 residues and one disulfide linkage between residues C8 and C19. We have previously determined the solution structure of SRP-1/2 using 2D ¹H-¹H NMR spectroscopy and nuclear Overhouser enhancement (NOE) derived distance constraints. The NMR structural studies showed a large number of NOE contacts between the side chain of residue 12 and the side chains of residues C8, P9 and C19 in both peptides. The high density of long-range NOE contacts for this residue (Y12 for SRP-1, and R12 for SRP-2) are similar to those of residue Y11 present in the Plasmocyte Spreading Peptide (PSP) of Pseudopulsia includes and Paralytic peptide (PP) from Manduca sexta. Earlier, studies suggested that residue Y11 plays an important role in the stabilization of PSP and PP structures. It was also observed that replacement of Y11 in PSP substantially reduced the biological activity in comparison to wild type. To better understand the role of residue Y12 and R12 in maintaining the structural stability of SRP-1 and SRP-2, we have conducted Molecular Dynamics Studies of SRP-1 and -2 wild type and select mutants (Y/R12A, Y/R12E, R12K, Y12R and R12Y). Our results indicate a more drastic increase in flexibility of the core region for all SRP1 mutants while the SRP-2 mutants showed dynamic characteristics relatively similar to wild type. Subsequent secondary structural characteristics analyses suggest that the increase in flexibility observed in SRP-1 mutants could be due to a drop in Beta strand formation propensity between residues Y12-R15 and F18-P21. Alpha helical propensity analyses of SRP-2 and mutants show a drastic change in alpha helix formation for SRP-2 mutants in comparison to wild type. This discrepancy in N-terminal alpha helix formation could be explained by a decrease in salt-bridge formation propensity for contacts D22-K7, and D24-K7 in SRP-2. Overall, our mutational analyses of SRP-1 and SRP-2 show that mutations at the embedded position have a more drastic impact on the rigidity and flexibility of SRP-1 than SRP-2. Infections by mosquito-borne diseases represent one of the leading causes of death in third world countries. The rapid progression of resistance to conventional insecticide causes a significant threat to the highly efficient preventive methods currently in place. Deletion of the Ecdysis Triggering Hormone (ETH) encoding gene has been proven to result in fatal deficits in Drosophila. Our current study explores the impact of point mutations on the structural integrity and function of ETH from the African Malaria Mosquito, Anopheles gambiae (AgETH). We herein have determined the solution structure of AgETH1 using 2D ¹H-¹H Nuclear Magnetic Resonance (NMR) spectroscopy and Nuclear Overhauser Effect (NOE) derived constraints. Our findings showed that the 17 amino acid peptide contains a short alpha helix between residues 3S and 11S. ETH is specifically characterized by the C-terminal motif PRXamide and sequence alignments of ETH peptides from several organisms suggests that the heavily conserved C-terminal PRXamide motif is critical for receptor activation. Seven mutations at various heavily conserved residue positions were performed to assess their subsequent effect on receptor activation by AgETH1. Our results show retention of peptide activity for mutants lacking the N-terminal region but containing the two highly conserved Lysine residues. These results suggest that the presence of the alpha helical structure observed for AgETH1 WT may be important for receptor activation. Furthermore, the activity assay results show that one of the highly conserved lysine residues (K12) may play a more critical role than the other (K9). Understanding peptide-receptor binding of AgETH1 will be a significant assistance for the development of insecticidal compounds that disrupt the ecdysis triggering hormone system that is a crucial component of larvae development specific to the insect species.
Keywords: SRP; Ecdysis; NMR; Molecular dynamics; Anopheles gambiae; Manduca sexta